Bio‐Physicochemical Dual Energy Harvesting Fabrics for Self‐Sustainable Smart Electronic Suits - Park, Jiwon; Chang, Sang‐Mi; Shin, Joonchul; Oh, In Woo; Lee, Dong‐Gyu; Kim, Hyun Soo; Kang, Heemin; Park, Yong Seok; Hur, Sunghoon; Kang, Chong‐Yun; Baik, Jeong Min; Jang, Ji‐Soo; et al. (Advanced energy materials, 2023)
Despite the rapid development of various wearable generators to harvest energy from human activity, they are limited to single or intermittent power generation. Here, stretchable and washable energy harvesting fabric is reported, which enables biomechanical and biochemical generation through co‐weaving triboelectric generator (TEG) and perspiration electric generator (PEG)‐based fibers. The two energy harvesting approaches can work individually or simultaneously, thereby combating humidity and increasing the electrical output. The maximum output power density of TEG‐ and PEG‐based fibers can achieve 166 and 5.4 µW cm−2, respectively. The woven‐structured patch‐type energy harvester is conformable with clothing. It can harvest energy from human movements and sweat to drive the wearable Internet of Things (IoT) without charging systems. This synergistic and complementary energy harvester can provide a viable standalone power source relying solely on human activity for wearable electronics. A woven‐structured energy harvester that operates using dual bio‐physicochemical sources is developed by co‐weaving triboelectric generator (TEG)‐based and perspiration electric generator (PEG)‐based fibers. These two types of fibers can work either individually or simultaneously, making them resistant to humidity and increasing their electrical output. The woven‐structured energy harvester can continuously power Internet of Things (IoT) devices and demonstrate remarkable washing durability.